Exosomes are possibly used as a tool of immune regulation during the dendritic cell-based immune therapy against HIV-I. (October 2016) - Ellwanger, Joel Henrique; Crovella, Sergio; dos Reis, Edione Cristina; Pontillo, Alessandra; Chies, José Artur Bogo
Abstract: Dendritic cell (DC)-based immune therapy (IT) against HIV showed variable results. It is known that different factors influence host response to DC-IT. Exosomes derived from DC are regulators of the immune system. In this context, here we hypothesize about the role of the DC-derived exosomes on the DC-IT response. Based on data from RT-PCR array genes expression (focused on the TSG101 gene, an exosome marker) and flow cytometry experiments of a DC-IT against HIV-1 clinical trial, we hypothesize that: During the DC-IT exosomes are used as an additional tool for immune system modulation. In addition, we believe that a low release of exosomes can be more beneficial for the DC-IT response than a high release of exosomes. Our data reinforce the concept that exosomes can act as an immune regulatory tool, however not in a generalized manner, but in a highly precise way. Our hypothesis is based in preliminary experimental data, thus, it should be tested using experimental and functional strategies involving a great number of patients. Once the hypothesis confirmed, the immunomodulatory role of the exosomes during DC-IT must be considered as an important factor in the (I) evaluation, (II) modulation, and (III) success of DC-IT against HIV.